Family-Initiated Pediatric Rapid Response: Characteristics, Impetus, and Outcomes. Issue 2 (March 2018) - Bavare, Aarti C.; Thomas, Jenilea K.; Elliott, Elizabeth P.; Morgan, Angela C.; Graf, Jeanine M.
Abstract : Brief Description: Family-initiated rapid response (FIRR) empowers families to express concern and seek care from specialized response teams. We studied FIRRs that occurred in a pediatric tertiary hospital over a 3-year period. The main aims were to describe the characteristics and outcomes of FIRRs and compare them with clinician-activated RRs (C-RRs). Of the 1, 906 RRs events reviewed, 49 (2.6%) were FIRRs. All FIRRs had appropriate clinical triggers with the most common being uncontrolled pain. Chronic conditions and previous admissions were present in 61%. More than half of FIRRs had a vital sign change that should have qualified C-RR activation. Seventy-six percent FIRRs needed at least one or more interventions. Twenty-seven percent of FIRRs needed transfer to intensive care unit compared with 60% transfer rate for C-RRs. Purpose of Submission/Relevance to Healthcare Quality: Family-initiated rapid response events were activated for legitimate concerns and frequently needed clinical interventions. Enhanced information and awareness of FIRR can improve utilization of the system and enhance family satisfaction, patient safety, and outcomes. Disseminating the information on FIRR and the importance of family involvement will improve the care of children and empower family members.